PENDEKATAN POLA GERAK DOMINAN DAN GAYA MENGAJAR DALAM PEMBELAJARAN SENAM DI SEKOLAH DASAR - Heri Purwanto (Departement of Sports Education, Faculty of Sport Sciences Yogyakarta State University, 2009)
This paper endeavor to describe gymnastics learning in Elementary school through dominant motion patterns and teaching style approach. Gymnastics learning is one of the course taught in physical education, sport, and health. Gymnastics learning aimed for developing students cognitive, affective, and psychomotor. Gymnastics learning in elementary school can be taught through dominant motion patterns and teaching style. Dominant motion pattern approach can be applied to gymnastics learning method based on gymnastics dominant movements series. Teaching style is a learning method which is developed from teacher centered to student centered. The use of the dominant motion patterns and learning style approach is expected to make gymnastics learning in elementary school become more active and enjoyable for students. The choose of good learning strategies will make learning more meaningful. Keywords: Gymnastics, Movement patterns, Teaching styles, Learning